KONTROL STRUKTUR PADA POLA â€œZIG-ZAGâ€ ALIRAN SUNGAI KAYAN DI DAERAH PESO, KALIMANTAN TIMUR - Baharuddin Baharuddin; Joko Wahyudiono (Jurnal Geologi dan Sumberdaya Mineral, 2007)
Peso Area is situated at the downstream of Kayan River, East Kalimantan. The area is generally occupied by a flysch-type deposit of Cretaceous Rajang-Embaluh Group. The unit is unconformably overlain by the Tertiary Sediments and is intruded by the Tertiary-Quaternary magmatics. Based on interpretation of landsat imagery, lineament features which represent faults can be traced outside the studied area. Based on landsat imagery data and result of joints, fault and fold analyses, it can be concluded that the zig-zag pattern of the Kayan River at Peso area is closely related to major faults movements. These faults are generally trending NE- SW and NW-SE.Â Keywords : structural control, zig-zag patterns, Kayan River